Perancangan SPK Kelayakan Pinjaman Koperasi Karyawan Perum Jasa Tirta Karya Bhakti Raharja dengan Metode MAUT - Rivaldy, Noval; Irmayanti, Dede; Defriani, Meriska (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Globalization that is happening is causing increasingly sharp free competition among economic actors, including cooperatives. Cooperatives until now continue to grow and become the mainstay of the community to turn the wheels of the economy during this pandemic and also experience various obstacles to run their business. However, under current conditions, in addition to very fast technological developments, cooperatives are also being pressured by the covid-19 pandemic, which causes cooperatives to be able to optimize digitalization. The loan eligibility decision support system applies the multi attribute utility theory (MAUT) method with 4 criteria or conditions that become the basis for decisions in the Perum Jasa Tirta Cooperative (PJTII) Karya Bhakti Raharja development model using the Extreme Programing method starting from the planning stage to the testing stage, using php programming language Data Flow Diagram (DFD) modeling. Loan Eligibility Decision Support System in PJT II Cooperatives to facilitate cooperative employees in determining loans to PJT II Employees. With this it is necessary to take advantage of a technological development, where how to make it easier for employees to make decisions from the assessment of the Multi Attribute Utility Theory (MAUT) method, because subjective assessments can be modeled and supported quickly.